PENGARUH PENERAPAN FULL DAY SCHOOL TERHADAP MOTIVASI BELAJAR SISWA DI SMA NEGERI 9 PEKANBARU - Intan Febriani; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This event will be based on research by the problems that arose fromobservations made by researchers, namely the low learning motivation of students thisis due with the application of full day school. Formulation of the problem in thisresearch is: How does the application of the Full Day School in SMA Negeri 9Pekanbaru, how learning motivation of students in SMA Negeri 9 Pekanbaru, howimplementation of Full Day School students learning motivation against in SMA Negeri9 Pekanbaru, how to influence the implementation of Full Day School students learningmotivation against in SMA Negeri 9 Pekanbaru. The purpose of the research to knowthe application of Full Day School in SMA Negeri 9 Pekanbaru, to know the learningmotivation of students in SMA Negeri 9 Pekanbaru, to know the relationship of theapplication of the Full Day School students learning motivation against in SMA Negeri9 Pekanbaru, to know how the implementation of Full Day School students learningmotivation against in SMA Negeri 9 Pekanbaru. The population in this research is theclass XI which amounted to 349 with a sample of 78 students. Data collectioninstruments namely observation, question form, interview and documentation. Dataanalysis with quantitative descriptive. Based on this research, there is a correlationbetween variables full day school with learning motivation variables can be expressedpositively then the direct relation. And can be known Fcount > Ftable, or simpleregression significance test turned out Fcount > Ftable or 27.716 > 3.97, then thehypothesis is rejected, meaning that there is a significant influence between theimplementation of full day school with learning motivation SMA Negeri 9 Pekanbaru.Keywords : Full Day School, Learning Motivation